2016
DOI: 10.1177/1971400916666559
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted coil embolisation for bilateral vertebral artery dissecting aneurysms presenting with subarachnoid haemorrhage

Abstract: Bilateral dissecting aneurysms presenting with subarachnoid haemorrhage are rare. The treatment strategy for bilateral vertebral artery dissecting aneurysms is controversial because the contralateral vertebral artery is already dissected and can easily undergo enlargement or bleed after non-reconstructive treatment procedures such as trapping or proximal occlusion. Here, we report a case of bilateral vertebral artery dissecting aneurysm presenting with subarachnoid haemorrhage that was treated with stent-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A large number of experiments have confirmed that stent-assisted coil embolization is safe, effective, and practical for the treatment of ruptured intracranial aneurysms [ 9 11 ]. Although complications are rare, some cases can experience serious adverse consequences [ 11 , 12 ]. Complications should be avoided as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experiments have confirmed that stent-assisted coil embolization is safe, effective, and practical for the treatment of ruptured intracranial aneurysms [ 9 11 ]. Although complications are rare, some cases can experience serious adverse consequences [ 11 , 12 ]. Complications should be avoided as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…With recent advances in device technologies, endovascular treatment has become the first-line treatment for vertebral artery dissecting aneurysms. [2,4,17,19] Endovascular treatments of vertebral artery dissecting aneurysms include internal trapping and stent-assisted coil embolization. In the present case, internal trapping was performed for the dissecting aneurysm of the right vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…[7-10,14,16,18] Bilateral occurrence of VAD is generally considered rare, but the number of reports of bilateral VAD has been increasing in recent years. [2,5,11,17,19] In this paper, we report a case of de novo VAD on the contralateral side presenting with subarachnoid hemorrhage (SAH) in the acute stage of cerebral infarction due to unilateral VAD.…”
Section: Introductionmentioning
confidence: 99%
“…This thereby avoids a dramatic increase in flow and haemodynamic stress in the contralateral IVADAs, which would otherwise likely contribute to high mortality. Ishikawa et al 33 reported a bilateral IVADAs case with SAH that the ruptured side was well treated with SAC, and the contralateral side was stable at follow-up after treatment. Such results might also support that reconstructive endovascular treatment has little impact on the haemodynamic stress to the contralateral IVADA.…”
Section: Era Of Reconstructive Endovascular Treatment For Bilateral Imentioning
confidence: 99%